Analisis Faktor-Faktor Yang Mempengaruhi Pendapatan Petani Di Desa Plampang Kecamatan Paiton - Fatmala, Kiki; Hukmah, Safiroh (Fakultas Ekonomi dan Bisnis Universitas Samudra, 2024)
This study aims to determine the effect of land area, labor and total cost on the income of farmers in Plampang village, Paiton sub-district. The research data used is primary data. The regression equation obtained is Y=-961600.747 + 29987.839 (La) + 139869.432 (Tk) + 350 (M).The results of t-test show that each variable of land area, labor and capital has a positive and significant effect on farmers' income in Plampang Village. The results of F test show that land area, labor and capital have a positive and significant effect on farmers' income in Plampang Village, Paiton Subdistrict. The coefficient of determination R Square is 0.913, which means that the variables of land area, labor and capital affect the income of farmers 91.3%.